2 sisters detective agency - Patterson, James, 1947-; Fox, Candice (Grand Central Publishing, 2021)
"Attorney Rhonda Bird returns home after a long estrangement when she learns her father has died. There she makes two important discoveries: her father stopped being an accountant and had opened up a private detective agency, and she has a teenage half sister named Baby. Baby brings in a client to the detective agency, a young man who claims he was abducted. During the course of the investigation, Rhonda and Baby become entangled in a dangerous case involving a group of overprivileged young adults who break laws for fun, their psychopath ringleader, and an ex-assassin victim who decides to hunt them down for revenge"--